Kepuasan Kerja Dipengaruhi Oleh Disiplin Kerja, Motivasi, Dan Komunikasi Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Balikpapan - Aulia Putri, Raydina; Hadiyatno, Didik; Cahyaning Putri Cipto, Rahajeng (Jurnal GeoEkonomi, 2025)
This research intends to see the influence of work discipline, motivation, and communication on employees' job satisfaction at BKPSDM Balikpapan. The population in this study is 61 employees, which are divided into 59 ASN and 2 non ASN at BKPSDM Balikpapan and the sample used consists of 59 ASN employees at BKPSDM Balikpapan. The analytical tool used is multiple linear regression with the help of smart PLS software and using purposive sampling technique with 59 respondents of ASN employees in BKPSDM Balikpapan. Data collection method is conducted by interview, observation and questionnaire distribution. The result of this study shows that work discipline variable has no partial effect on employee job satisfaction in BKPSDM Balikpapan, motivation variable has partial effect on employee job satisfaction in BKPSDM Balikpapan, and communication variable has no partial effect on employee job satisfaction in BKPSDM Balikpapan.